Vertical and temporal distribution of spotted‐wing drosophila (Drosophila suzukii) and pollinators within cultivated raspberries. Issue 8 (12th March 2019) - Jaffe, Benjamin D; Guédot, Christelle
Abstract: BACKGROUND: Drosophila suzukii (Diptera: Drosophilidae) is the most prominent arthropod pest of caneberries. Current management practices rely on chemical control, which has raised concerns over the sustainability of this approach. We currently understand little about D. suzukii activity, and whether activity patterns can be exploited to improve management. In this study, we investigated the vertical and temporal distribution of D. suzukii, as well as pollinators, in cultivated raspberries. RESULTS: D. suzukii were generally crepuscular, and most active in the morning within the bottom half of the crop, and in the evening within the top half of the crop. Pollinators were most active during the day and within the top half of the canopy. Humidity and temperature were correlated with insect activity. CONCLUSION: Pesticides applied during twilight that ensure coverage in the bottom half of the crop, or if applied in the late afternoon cover the entire crop, should improve the pesticide efficacy. However, previous studies suggest that specific D. suzukii (e.g. sex, mating status, age) may exploit different areas in the crop at different times, and more work needs to be done to understand how these aspects before a specific management program can be recommended. © 2019 Society of Chemical Industry Abstract : Spotted‐wing drosophila and bees are active at different heights and times of day. Pest management might be improved by targeting the times and locations when flies are active and bees are not.